(untitled) (المجلة الدولية للعلوم المالية والإدارية والاقتصادية, 2026)
This study examines corporate governance in private companies in the Kingdom of Saudi Arabia and analyzes its role in improving institutional performance efficiency amid the Kingdom’s economic and regulatory transformations. Adopting a descriptive–analytical approach, the study synthesizes relevant academic literature and prior research and reviews key governance-related regulatory and institutional orientations in the Saudi context. The analysis indicates that the effective implementation of governance principles—especially transparency, accountability, and the protection of stakeholder rights—tends to strengthen institutional performance efficiency and enhance organizational sustainability. At the same time, the review suggests persistent implementation challenges in private (particularly non-listed) companies, including uneven compliance, limited formalization of governance practices, and constraints related to governance capabilities and internal control maturity. The study recommends strengthening governance awareness in private companies, institutionalizing governance through documented policies and oversight mechanisms, and promoting flexible governance frameworks that can be tailored to company size, ownership concentration, and operational complexity.